Trends of inpatient palliative care use among hospitalized patients with Parkinson's disease. (August 2020) - Di Luca, Daniel G.; Feldman, Matthew; Jimsheleishvili, Sopiko; Margolesky, Jason; Cordeiro, Joacir Graciolli; Diaz, Anthony; Shpiner, Danielle S.; Moore, Henry P.; Singer, Carlos; Li, Hua; Luca, Corneliu
Abstract: Introduction: Palliative care in Parkinson's Disease (PD) is an effective intervention to improve quality of life, although historically, access and availability have been very restricted. Methods: We performed a retrospective cohort study using the National Inpatient Sample (NIS) data from 2007 to 2014. Diagnostic codes were used to identify patients with PD and palliative care referral. Trends were calculated and logistic analysis performed to identify predictors of palliative care use. Results: We identified 397, 963 hospitalizations from 2007 to 2014 for patients with PD. Of these, 10, 639 (2.67%) were referred to palliative care. The rate of consultation increased from 0.85% in 2007 to 4.49% in 2014. For 1 unit in year increase, there was 1.23 time the odds of receiving palliative consultation (OR 1.23, CI 1.21–1.25, p < 0.0001). Hispanics (OR 0.90, CI 0.81–1.01, p = 0.0550), Black (OR 0.90, CI 0.81–1.01, p = 0.0747) and White patients had similar rates of referral after adjustment. Women were less likely to be referred to palliative care (OR 0.90, CI 0.87–0.94, p < 0.0001). Other factors strongly associated with a higher rate of referrals included private insurance when compared to Medicare (OR 2.14, CI 1.89–2.41, p < 0.0001) and higher income (OR 1.41, CI 1.30–1.53, p < 0.0001). Conclusion: There has been a significant increase in palliative care referrals among hospitalized patients with PD in the US, although the overall rate remains low. After controlling for confounders, racial and ethnic disparities were not found. Women, patients with Medicare/Medicaid, and those with lower income were less likely to be referred to palliative care. Highlights: There has been an increase in inpatient palliative care use among patients with PD. Women with PD were less likely to be referred to palliative care. Palliative consult was higher in patients with private insurance and higher income. No racial or ethnic disparities were found in palliative care referral.